Multiple Autoantibodies Display Association with Lymphopenia, Proteinuria, and Cellular Casts in a Large, Ethnically Diverse SLE Patient Cohort. (4th September 2012) - Lu, Rufei; Robertson, Julie M.; Bruner, Benjamin F.; Guthridge, Joel M.; Neas, Barbara R.; Nath, Swapan K.; Kelly, Jennifer A.; Moser Sivils, Kathy L.; Chakravarty, Eliza F.; Kamen, Diane L.; Gilkeson, Gary S.; Wallace, Daniel J.; et al.
Abstract : Purpose . This study evaluates high-throughput autoantibody screening and determines associated systemic lupus erythematosus (SLE) clinical features in a large lupus cohort. Methods . Clinical and demographic information, along with serum samples, were obtained from each SLE study participant after appropriate informed consent. Serum samples were screened for 10 distinct SLE autoantibody specificities and examined for association with SLE ACR criteria and subcriteria using conditional logistic regression analysis. Results . In European-American SLE patients, autoantibodies against 52 kD Ro and RNP 68 are independently enriched in patients with lymphopenia, anti-La, and anti-ribosomal P are increased in patients with malar rash, and anti-dsDNA and anti-Sm are enriched in patients with proteinuria. In African-American SLE patients, cellular casts associate with autoantibodies against dsDNA, Sm, and Sm/nRNP. Conclusion . Using a high-throughput, bead-based method of autoantibody detection, anti-dsDNA is significantly enriched in patienets with SLE ACR renal criteria as has been previously described. However, lymphopenia is associated with several distinct autoantibody specificities. These findings offer meaningful information to allow clinicians and clinical investigators to understand which autoantibodies correlate with select SLE clinical manifestations across common racial groups using this novel methodology which is expanding in clinical use.